Nees, Lawrence. 2023. Illuminating the Word in the Early Middle Ages. Cambridge: Cambridge University Press. Pp. xxx + 558. ISBN 9781009193863. - Palmer, James (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2024)
Book review of Nees, Lawrence. 2023. Illuminating the Word in the Early Middle Ages. Cambridge: Cambridge University Press. Pp. xxx + 558. ISBN 9781009193863.